2018
DOI: 10.18632/oncotarget.26036
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of non-muscle-invasive bladder cancer recurrence by measurement of checkpoint HLAG’s receptor ILT2 on peripheral CD8+ T cells

Abstract: Background and ObjectiveRecurrence of non-muscle invasive bladder cancer (NMIBC) after initial management occurs in 60–70% of patients. Predictive criteria for recurrence remain only clinical and pathological. The aim of this study was to investigate the prognostic significance of the proportion of checkpoint HLA-G’s receptor ILT2-expressing peripheral CD8+ T cells.ResultsThe proportion of CD4+ILT2+and CD8+ILT2+ T cells was not increased in NMIBC compared to controls. However, a strong association was found be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…9 10 Previous studies also reported that there is a strong association between the percentage of circulating CD8 + LILRB1 T cells and the recurrence risk of non-muscle-invasive bladder cancer. 41 Taken together, our results and previous reports suggest that LILRB1 expression on NK cells and T cells has prognostic value.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…9 10 Previous studies also reported that there is a strong association between the percentage of circulating CD8 + LILRB1 T cells and the recurrence risk of non-muscle-invasive bladder cancer. 41 Taken together, our results and previous reports suggest that LILRB1 expression on NK cells and T cells has prognostic value.…”
Section: Discussionsupporting
confidence: 86%
“… 9 10 Previous studies also reported that there is a strong association between the percentage of circulating CD8 + LILRB1 T cells and the recurrence risk of non-muscle-invasive bladder cancer. 41 Taken together, our results and previous reports suggest that LILRB1 expression on NK cells and T cells has prognostic value. Although the precise mechanism of the LILRB1 polymorphism in human NK cells is unknown, the expression of LILRB1 on NK cells is linked to particular haplotypes and a polymorphic regulatory region.…”
Section: Discussionsupporting
confidence: 86%
“…Its main receptor is ILT2/CD85j and it is expressed on some T lymphocytes: the bond between the ligand and its receptor suppresses the function of natural-killer cells, dendritic cells, cytotoxic T lymphocytes, CD4 + T lymphocytes and the proliferation of T cells. A recent study ( 34 ) analyzed the role of ILT2 on recurrence in non-muscle invasive BCa. This study reported a significant association between the proportion of circulating CD8 + ILT2 + T cells and risk of recurrence.…”
Section: Cytokines and Immunological Markersmentioning
confidence: 99%
“…Moreover, Gonen-Gross et al (41) discovered that the b2microglobulin-free form of HLA-G also forms disulfide-linked dimers and multimers on the cell surface similar to the dimer form of normal b2microglobulin-associated HLA-G protein, which we demonstrated above in our study. Because b2microglobulin forms a major contact site between LILRB1 and HLA-G that is specific for LILRB1 only, the b2microglobulin-free form may not provide inhibitory signaling through predicting recurrence in bladder cancer (44). However, in our study, we could not determine a significant difference in CD8 + LILRB1 + T cells between RJ and NR groups that excludes these cells as potential marker for kidney graft survival.…”
Section: Discussionmentioning
confidence: 55%
“…LILRB receptor has potent immunosuppressive effects capable of suppressing alloantigen‐activated T cells and inhibiting TCMR. Recent studies have identified CD8 + LILRBl + T cells in the peripheral blood as a possible biomarker for predicting recurrence in bladder cancer (44). However, in our study, we could not determine a significant difference in CD8 + LILRB1 + T cells between RJ and NR groups that excludes these cells as potential marker for kidney graft survival.…”
Section: Discussionmentioning
confidence: 99%